Determinación del costo de un menú semanal para la empresa Restaurante Gualanday. (2022)
All businesses, in order to continue advancing and obtain profits, must clearly know the production cost of each of the goods and services offered and control this variable within the establishment, but in a market that varies continuously, this task becomes increasingly difficult. further.